2020
DOI: 10.1016/j.heliyon.2020.e03303
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antibacterial activity of medicinal plants against biofilm-forming methicillin-resistant Staphylococcus aureus: efficacy of Moringa stenopetala and Rosmarinus officinalis extracts

Abstract: The prevalence of methicillin-resistant Staphylococcus aureus (MRSA) is slowly rising in Ethiopia for the past few decades. Therefore, novel classes of antibiotics are indispensable to combat the increased incidence of newly emerging multidrug-resistant bacteria like MRSA. Terrestrial flora is considered as a reservoir of novel bioactive secondary metabolites as they have provided us with the largest array of natural products. In this background, the present study is intended to evaluate the in-vitro antibacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 42 publications
3
48
0
1
Order By: Relevance
“…The promising antibacterial activities observed by the methanol extract in could be due to the variation in the number of antibacterial constituents in the extract because of the polarity of methanol and solubility of the compounds in it in comparison to other solvents. 30 Similar findings were observed other studies. 31,32 The promising results demonstrated by the methanolic extract prompted us to evaluate its MIC and MBC using microdillition method.…”
Section: Antibacterial Activitysupporting
confidence: 88%
“…The promising antibacterial activities observed by the methanol extract in could be due to the variation in the number of antibacterial constituents in the extract because of the polarity of methanol and solubility of the compounds in it in comparison to other solvents. 30 Similar findings were observed other studies. 31,32 The promising results demonstrated by the methanolic extract prompted us to evaluate its MIC and MBC using microdillition method.…”
Section: Antibacterial Activitysupporting
confidence: 88%
“…AMP11) was done from the local markets of Arba Minch town, Gamo Gofa zone of Ethiopia. The plant specimen was botanically authenticated as previously indicated [ 15 ]. It was identified to the genus and species level with the aid of an eminent plant taxonomist (Dr. Remesh Moochikkal, Jazan University, Kingdom of Saudi Arabia).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the leaves of this plant find frequent application as a flavouring agent in local traditional meat dishes both cooked and raw. Results obtained from our previous study showed that the EtOH extract of R. officinalis has anti-methicillin resistant S. auerus activity [ 15 ]. To acquire more relevant data related to its antimicrobial activity, further comprehensive evaluations are imperative.…”
Section: Introductionmentioning
confidence: 99%
“…The MIC was determined as the lowest concentration of extract that completely inhibited the growth of the MRSA detected by the unaided eye (Valle et al 2015). MBC was defined as the concentration which exhibits zero growth of the colonies compared to the culture of the initial inoculum of the same strain (Manilal et al 2020;Prastiyanto et al 2020b). The Wells were subcultured using a 10 µL inoculating loop on to a BAP at (35 ± 2) o C for 16-20 h incubation.…”
Section: Minimum Inhibitory Concentrations (Mic) and Minimum Bactericmentioning
confidence: 99%